1976
DOI: 10.1111/j.1469-8137.1976.tb01445.x
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES ON THE NUTRITION AND GROWTH OF DROSERA SPECIES WITH REFERENCE TO THE CARNIVOROUS HABIT

Abstract: SUMMARY Drosera whittakeri was grown in sand cultures supplemented with inorganic salt solutions lacking either nitrogen, sulphur, phosphorus or the microelements. Application of the insect Drosophila melanogaster to the tentacles of plants raised on nitrogen or sulphur deficient medium, enhanced growth, which on nitrogen deficient medium was accompanied by decreased nitrogen content per unit weight although the total nitrogen per plant was unaffected. Application of insects to plants on media deficient in ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

1976
1976
2008
2008

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 20 publications
3
46
0
1
Order By: Relevance
“…We would argue that our design better addresses the biological importance of insectivory in that it more closely resembles natural insectivory and substrate nutrient conditions. Compared with North American sundew species that are almost always found in nutrient-poor soils, D. binata may grow in relatively rich soils (Chandler & Anderson 1976). For example, native soils of Drosera binata may contain 10 times more phosphorus and nitrogen than North American sundew bog soils (Stewart 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We would argue that our design better addresses the biological importance of insectivory in that it more closely resembles natural insectivory and substrate nutrient conditions. Compared with North American sundew species that are almost always found in nutrient-poor soils, D. binata may grow in relatively rich soils (Chandler & Anderson 1976). For example, native soils of Drosera binata may contain 10 times more phosphorus and nitrogen than North American sundew bog soils (Stewart 1990).…”
Section: Discussionmentioning
confidence: 99%
“…This flexibility of Drosera in regards to nutrient source has been shown elsewhere. For example, when insects were not available, Drosera obtained all of its nutrient requirements through roots (Chandler & Anderson 1976;Small et al 1977). found that D. erythrorhiza was able to exploit nutrient surges via soil after fire.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, nitrogen-containing insect metabolites appeared to be more eective in promoting the ®tness of plants growing on the rocks than on an enriched substrate. Chandler and Anderson (1976) found that the addition of inorganic nitrate to Drosera whittakeri and Drosera binata plants supplied with insects even inhibited absolute growth, and the greatest absolute growth was attained in the presence of insects at low nitrate concentrations. A gradient of responses was also found for mucilage secretion in plants growing on the rocky wall with respect to Prey factor: from Prey-exclusion (the minimum) to Prey-addition (the maximum; Fig.…”
Section: Plant Responses To Prey and Inorganic Nutrientsmentioning
confidence: 99%
“…Some species appear to be highly dependent on insect prey, whereas others can survive to maturity and even¯ower in the absence of any nutrient of animal origin (LuÈ ttge 1983;Givnish 1989). In fact, laboratory and ®eld experimentation has indicated that several Pinguicula and Drosera species are facultative carnivores, their growth being stimulated both by prey and mineral nutrients (Chandler and Anderson 1976;Aldenius et al 1983;Karlsson and Carlsson 1984;Karlsson et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Drosera whittakeri was grown in sand cultures as described by Chandler and Anderson (1976), using solution A except that the concentration of all the salts in the nutrient solution was decreased three-fold. Leaf material, for enzyme studies, was harvested from sites 20 km north-east and 50 km north of Melbourne.…”
Section: Plant Materialsmentioning
confidence: 99%